Electrochemical device and electronic device
By using silicon-carbon composite material with modulated particle size and surface layer in the negative electrode material layer of the lithium-ion battery, the problem of damage to the SEI film in the lithium-ion battery is solved, and the cycle performance and rate performance of the battery are improved.
Patent Information
- Application Number
- CN202510099582.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-03-18
AI Technical Summary
The existing lithium-ion batteries are easily damaged due to the volume expansion of the silicon-based negative electrode material during the lithium-embedding or deliquification process, which causes the solid electrolyte interface (SEI) film to be affected by high stress, which in turn consumes lithium ions and affects the cycling performance of the battery.
A negative electrode material layer including the first silicon-carbon composite material and the second silicon-carbon composite material is adopted. The average particle size of the first silicon-carbon composite material is 2 μm to 6 μm, and the average particle size of the second silicon-carbon composite material is 7 μm to 20 μm, and a fluorine-containing material layer and a carbon material layer are respectively provided on the surface of the particles to form a stable SEI film.
By regulating the particle size and surface layer thickness of the siliceous carbon composite material, the room temperature cycling performance, low temperature cycling performance and rate performance of the electrochemical device are improved, the damage of the SEI film is reduced, and the service life of the battery is extended.
Smart Images

Figure BDA0005254247830000221 
Figure BDA0005254247830000231 
Figure BDA0005254247830000241
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to an electrochemical device and an electronic device. Background Art
[0002] With the development of new energy technologies, electrochemical devices (such as lithium-ion batteries) are increasingly used in mobile phones, computers and other fields, and people have also put forward higher requirements for them. Commercial lithium-ion batteries based on graphite anode materials are close to their theoretical limits and are difficult to meet the current mobile information society's demand for high-energy density batteries. Silicon anode materials are considered to be the most promising and competitive emerging anode materials due to their relatively low discharge potential, high theoretical specific capacity and abundant reserves.
[0003] However, due to the volume expansion of the silicon-based negative electrode during the lithium insertion or de-lithiation process, the solid electrolyte interface (SEI) film is often affected by high stress and strain, which makes the SEI film easily damaged and consumes lithium ions during cycling. Therefore, it is necessary to establish an elastic and rigid SEI film on the surface of the silicon-based negative electrode. In summary, it is urgent to provide a negative electrode material with high specific capacity and conductivity to improve the room temperature cycle performance, low temperature cycle performance and rate performance of lithium-ion batteries, while allowing lithium-ion batteries to have a higher volume energy density. Summary of the invention
[0004] The purpose of the present application is to provide an electrochemical device and an electronic device to improve the room temperature cycle performance, low temperature cycle performance and rate performance of the electrochemical device.
[0005] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of electrochemical devices to explain this application, but the electrochemical devices of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:
[0006] The first aspect of the present application provides an electrochemical device, the electrochemical device includes an electrolyte and a negative electrode plate, the negative electrode plate includes a negative electrode material layer, the negative electrode material layer includes a first silicon-carbon composite material and a second silicon-carbon composite material, the first silicon-carbon composite material includes first silicon-carbon particles and a fluorine-containing material layer located on the surface of the first silicon-carbon particles, and the second silicon-carbon composite material includes second silicon-carbon particles and a carbon material layer located on the surface of the second silicon-carbon particles. The average particle size of the first silicon-carbon composite material is 2μm to 6μm; the average particle size of the second silicon-carbon composite material is 7μm to 20μm. When the fluorine-containing material layer and the carbon material layer are respectively arranged on the surfaces of the first silicon-carbon particles and the second silicon-carbon particles, and the average particle sizes of the first silicon-carbon composite material and the second silicon-carbon composite material are regulated within the above range, the room temperature cycle performance, low temperature cycle performance and rate performance of the electrochemical device can be improved.
[0007] In one embodiment of the present application, the average particle size of the first silicon-carbon composite material is 2 μm to 4 μm, and the average particle size of the second silicon-carbon composite material is 7 μm to 11 μm. When the average particle sizes of the first silicon-carbon composite material and the second silicon-carbon composite material are within the above range, the room temperature cycle performance, low temperature cycle performance and rate performance of the electrochemical device can be further improved.
[0008] In one embodiment of the present application, the cross section of the negative electrode sheet includes a counting region, and the area of the counting region is 19200 μm 2 , in the counting area, the number of particles of the first silicon-carbon composite material is N1, 20≤N1≤100. When N1 is within the above range, the first cycle charge and discharge efficiency of the first silicon-carbon composite material and the second silicon-carbon composite material can be improved, the room temperature cycle performance and low temperature cycle performance of the electrochemical device can be improved, and the small particles can be more fully filled between the large particles, thereby improving the volume energy density of the electrochemical device.
[0009] In one embodiment of the present application, the number of particles of the first silicon-carbon composite material is N1, the number of particles of the second silicon-carbon composite material is N2, and 0.18≤N1 / (N1+N2)≤0.67. When the value of N1 / (N1+N2) is within the above range, the first cycle charge and discharge efficiency of the first silicon-carbon composite material and the second silicon-carbon composite material can be further improved, and the room temperature cycle performance and low temperature cycle performance of the electrochemical device can be further improved; and the small particles can be more fully filled between the large particles, thereby improving the volume energy density of the electrochemical device.
[0010] In one embodiment of the present application, the average thickness D1 of the fluorine-containing material layer is 10 nm to 25 nm, preferably 14 nm to 21.2 nm. When the value of D1 is within the above range, it is conducive to the formation of a LiF-rich SEI film, thereby improving the room temperature cycle performance, low temperature cycle performance and rate performance of the electrochemical device.
[0011] In one embodiment of the present application, the average thickness D2 of the carbon material layer is 8.4 nm to 13.7 nm, preferably 9.5 nm to 12.6 nm. When the value of D2 is within the above range, it is beneficial to improve the stability of the SEI film, improve the kinetic performance of the electrochemical device, and at the same time, it can increase the gram capacity of the second silicon-carbon composite material and improve the room temperature cycle performance and low temperature cycle performance of the electrochemical device.
[0012] In one embodiment of the present application, the fluorine-containing material layer comprises at least one of poly(methyl-3,3,3-trifluoropropylsiloxane) or perfluoropolyether; the carbon material layer comprises at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes or graphene. When the fluorine-containing material layer comprises the above materials, it is conducive to the formation of a LiF-rich SEI film, thereby further improving the room temperature cycle performance, low temperature cycle performance and rate performance of the electrochemical device; when the carbon material layer comprises the above materials, it can further improve the stability of the SEI film, and can also improve the ionic conductivity of the second silicon-carbon composite material, and improve the kinetic performance of the electrochemical device.
[0013] In one embodiment of the present application, based on the mass of the first silicon-carbon composite material, the mass percentage of fluorine element is 0.05% to 2%. When the mass percentage of fluorine element is within the above range, it is beneficial to form a LiF-rich SEI film, and improve the room temperature cycle performance, low temperature cycle performance and rate performance of the electrochemical device.
[0014] In one embodiment of the present application, the mass percentage of silicon in the first silicon-carbon particles is 38% to 50%, and the mass percentage of silicon in the second silicon-carbon particles is 42% to 60%. When the mass percentage of silicon in the first silicon-carbon particles and the mass percentage of silicon in the second silicon-carbon particles are within the above range, the gram capacity of the first silicon-carbon composite material and the second silicon-carbon composite material can be increased, the volume energy density of the electrochemical device can be increased, and the consumption of the electrolyte during the cycle can be reduced, the room temperature cycle performance and low temperature cycle performance of the electrochemical device can be improved, and the kinetic performance and rate performance of the electrochemical device can also be improved.
[0015] In one embodiment of the present application, the compaction density of the negative electrode sheet is 1.6 g / cm 3 Up to 1.8g / cm 3 When the compaction density of the negative electrode sheet is within the above range, it is beneficial to improve the dynamic performance of the negative electrode sheet and enhance the energy density of the electrochemical device.
[0016] In one embodiment of the present application, the electrolyte includes sulfolane, and the mass percentage of sulfolane is 0.12% to 0.48% based on the mass of the electrolyte. When the mass percentage of sulfolane is within the above range, it is beneficial to generate an inorganic SEI interface rich in sulfur elements, and improve the room temperature cycle performance and low temperature cycle performance of the electrochemical device.
[0017] In one embodiment of the present application, the electrolyte includes fluoroethylene carbonate, and the mass percentage of fluoroethylene carbonate is 8% to 20%, preferably 12.5% to 17.5%, based on the mass of the electrolyte. When the mass percentage of fluoroethylene carbonate is within the above range, it can improve the protection of the negative electrode plate, reduce the cycle gas production, and thus improve the room temperature cycle performance and low temperature cycle performance of the electrochemical device.
[0018] The second aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. The electronic device of the present application has good room temperature cycle performance, low temperature cycle performance and rate performance.
[0019] Beneficial effects of this application:
[0020] The present application provides an electrochemical device and an electronic device, wherein the electrochemical device includes an electrolyte and a negative electrode plate, wherein the negative electrode plate includes a negative electrode material layer, wherein the negative electrode material layer includes a first silicon-carbon composite material and a second silicon-carbon composite material, wherein the first silicon-carbon composite material includes first silicon-carbon particles and a fluorine-containing material layer located on the surface of the first silicon-carbon particles, and wherein the second silicon-carbon composite material includes second silicon-carbon particles and a carbon material layer located on the surface of the second silicon-carbon particles. The average particle size of the first silicon-carbon composite material is 2 μm to 6 μm; the average particle size of the second silicon-carbon composite material is 7 μm to 20 μm. When a fluorine-containing material layer and a carbon material layer are respectively arranged on the surfaces of the first silicon-carbon particles and the second silicon-carbon particles, and when the average particle sizes of the first silicon-carbon composite material and the second silicon-carbon composite material are regulated within the above range, the room temperature cycle performance, low temperature cycle performance and rate performance of the electrochemical device can be improved.
[0021] Of course, implementing any product or method of the present application does not necessarily require achieving all of the above advantages at the same time. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0023] It should be noted that in the specific embodiments of the present application, a lithium-ion battery is used as an example of an electrochemical device to explain the present application, but the electrochemical device of the present application is not limited to a lithium-ion battery.
[0024] The first aspect of the present application provides an electrochemical device, which includes an electrolyte and a negative electrode plate, the negative electrode plate includes a negative electrode material layer, the negative electrode material layer includes a negative electrode active material, the negative electrode active material includes a first silicon-carbon composite material and a second silicon-carbon composite material, the first silicon-carbon composite material includes a first silicon-carbon particle and a fluorine-containing material layer located on the surface of the first silicon-carbon particle, and the second silicon-carbon composite material includes a second silicon-carbon particle and a carbon material layer located on the surface of the second silicon-carbon particle. The fluorine-containing material layer may be located on part or all of the surface of the first silicon-carbon particle, and the carbon material layer may be located on part or all of the surface of the second silicon-carbon particle. The average particle size of the first silicon-carbon composite material is 2 μm to 6 μm, preferably 2 μm to 4 μm; the average particle size of the second silicon-carbon composite material is 7 μm to 20 μm, preferably 7 μm to 11 μm. For example, the average particle size of the first silicon-carbon composite material can be 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm or a range consisting of any two of the values therein; the average particle size of the second silicon-carbon composite material can be 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm or a range consisting of any two of the values therein.
[0025] The inventors have found that when the negative electrode sheet of the electrochemical device contains both silicon-carbon particles with a smaller average particle size and silicon-carbon particles with a larger average particle size, the compaction density of the negative electrode sheet can be improved, but it is not conducive to the cycle performance of the electrochemical device. The inventors speculate that the silicon-carbon particles with a smaller average particle size have a larger contact area with the electrolyte, thus producing more side reactions, increasing the consumption of the electrolyte and forming an SEI film with excessive thickness; the silicon-carbon particles with a larger average particle size expand and contract during the charging and discharging process, and the surface of the silicon-carbon particles produces a greater degree of displacement, which can easily cause the SEI film to rupture and the conductive network to break. Providing a fluorine-containing material layer on the surface of the first silicon-carbon particles with a smaller average particle size is conducive to the formation of a LiF-rich SEI film, reducing the contact between the first silicon-carbon particles and the electrolyte, reducing the side reactions between the first silicon-carbon particles and the electrolyte, and effectively inhibiting the expansion of the first silicon-carbon particles, thereby improving the low-temperature cycle performance and rate performance of the electrochemical device. Arranging a carbon material layer on the surface of the second silicon-carbon particles with a larger average particle size can improve the stability of the SEI film, effectively inhibit the expansion of the second silicon-carbon particles, and can also improve the electronic conductivity of the second silicon-carbon composite material and the kinetic performance of the electrochemical device. Arranging a fluorine-containing material layer and a carbon material layer on the surface of the first silicon-carbon particles and the second silicon-carbon particles respectively, respectively obtaining the first silicon-carbon composite material and the second silicon-carbon composite material, when the average particle size of the first silicon-carbon composite material and the second silicon-carbon composite material is within the above range, the first silicon-carbon composite material and the second silicon-carbon composite material have a suitable specific surface area, adjust the contact degree between the negative electrode active material and the electrolyte, reduce the occurrence of side reactions, improve the first cycle charge and discharge efficiency of the first silicon-carbon composite material and the second silicon-carbon composite material, and improve the room temperature cycle performance and low temperature cycle performance of the electrochemical device; at the same time, it can also improve the ionic conductivity and rate performance of the negative electrode active material. The fluorine-containing material layer and the carbon material layer are arranged on the surface of the first silicon-carbon particle and the second silicon-carbon particle, respectively, which is conducive to controlling the content of the fluorine-containing material layer and the carbon material layer. The first silicon-carbon composite material and the second silicon-carbon composite material are mixed in proportion, which can provide more active sites for the embedding of lithium ions, shorten the diffusion path of lithium ions between particles, and improve the kinetic performance of the electrochemical device; and the new interface generated by the volume change of the two is reduced, the contact degree between the negative electrode active material and the electrolyte is adjusted, the occurrence of side reactions is reduced, the first cycle charge and discharge efficiency of the first silicon-carbon composite material and the second silicon-carbon composite material is improved, and the room temperature cycle performance and low temperature cycle performance of the electrochemical device are improved; in addition, the small particles are more fully filled between the large particles, which improves the volume energy density of the electrochemical device. In this application, "low temperature" refers to a temperature of ≤-10°C.
[0026] In one embodiment of the present application, the cross section of the negative electrode sheet includes a counting region, and the area of the counting region is 19200 μm 2In the counting area, the number of particles of the first silicon-carbon composite material is N1, 20≤N1≤100. The counting area can be one area or multiple areas. When the counting area is multiple areas, the sum of the areas of the multiple areas is 19200 μm 2 . For example, the value of N1 can be 20, 30, 40, 50, 60, 70, 80, 90, 100 or a range consisting of any two of these values. When N1 is within the above range, the contact degree between the negative electrode active material and the electrolyte can be adjusted, the side reaction between the negative electrode active material and the electrolyte can be reduced, the first cycle charge and discharge efficiency of the first silicon-carbon composite material and the second silicon-carbon composite material can be improved, the room temperature cycle performance and low temperature cycle performance of the electrochemical device can be improved, and the small particles can be more fully filled between the large particles, thereby improving the volume energy density of the electrochemical device.
[0027] In one embodiment of the present application, the number of particles of the first silicon-carbon composite material is N1, the number of particles of the second silicon-carbon composite material is N2, and 0.18≤N1 / (N1+N2)≤0.67. For example, the value of N1 / (N1+N2) can be 0.18, 0.2, 0.3, 0.4, 0.5, 0.6, 0.67 or a range consisting of any two of these values. When the value of N1 / (N1+N2) is within the above range, the contact degree between the negative electrode active material and the electrolyte can be adjusted after mixing large and small particles, reducing the side reaction between the negative electrode active material and the electrolyte, further improving the first cycle charge and discharge efficiency of the first silicon-carbon composite material and the second silicon-carbon composite material, and further improving the room temperature cycle performance and low temperature cycle performance of the electrochemical device; and allowing small particles to be more fully filled between large particles to improve the volume energy density of the electrochemical device.
[0028] In one embodiment of the present application, based on the mass of the negative electrode active material, the mass percentage of the first silicon-carbon composite material is 10% to 50%, the mass percentage of the second silicon-carbon composite material is 50% to 90%, and the mass ratio of the first silicon-carbon composite material to the second silicon-carbon composite material is 1:9 to 1:1, preferably 1:4 to 2:3. For example, the mass percentage of the first silicon-carbon composite material can be 10%, 20%, 30%, 40%, 50%, or a range consisting of any two values therein, the mass percentage of the second silicon-carbon composite material can be 50%, 60%, 70%, 80%, 90%, or a range consisting of any two values therein, and the mass ratio of the first silicon-carbon composite material to the second silicon-carbon composite material can be 1:9, 1:8, 1:4, 3:7, 2:3, 1:1, or a range consisting of any two values therein. When the mass percentage of the first silicon-carbon composite material, the mass percentage of the second silicon-carbon composite material, and the mass ratio of the first silicon-carbon composite material to the second silicon-carbon composite material are within the above range, the degree of contact between the negative electrode active material and the electrolyte can be adjusted, thereby reducing the side reaction between the negative electrode active material and the electrolyte, further improving the first-cycle charge and discharge efficiency of the first silicon-carbon composite material and the second silicon-carbon composite material, and further improving the room temperature cycle performance and low-temperature cycle performance of the electrochemical device; and small particles can be more fully filled between large particles, thereby improving the volume energy density of the electrochemical device.
[0029] In one embodiment of the present application, the average thickness D1 of the fluorine-containing material layer is 10nm to 25nm, preferably 14nm to 21.2nm. For example, the value of D1 can be 10nm, 12nm, 14nm, 16nm, 18nm, 20nm, 21.2nm, 22nm, 24nm, 25nm or a range consisting of any two of the values. When the value of D1 is within the above range, the fluorine-containing material layer on the surface of the first silicon-carbon particle has a suitable average thickness, and the fluorine-containing material layer has a suitable mass percentage, which is conducive to the formation of a LiF-rich SEI film, reduces the side reaction of the first silicon-carbon particle with the electrolyte, and effectively inhibits the expansion of the first silicon-carbon particle, thereby improving the room temperature cycle performance, low temperature cycle performance and rate performance of the electrochemical device.
[0030] In one embodiment of the present application, the average thickness D2 of the carbon material layer is 8.4nm to 13.7nm, preferably 9.5nm to 12.6nm. For example, the value of D2 can be 8.4nm, 9nm, 9.5nm, 10nm, 11nm, 12nm, 12.6nm, 13nm, 13.7nm or a range consisting of any two of the values. When the value of D2 is within the above range, the carbon material layer on the surface of the second silicon-carbon particle has a suitable average thickness, and the carbon material layer has a suitable mass percentage, which is beneficial to improve the stability of the SEI film, effectively inhibit the expansion of the second silicon-carbon particle during the cycle, and improve the kinetic performance of the electrochemical device. At the same time, it can increase the gram capacity of the second silicon-carbon composite material, and improve the room temperature cycle performance and low temperature cycle performance of the electrochemical device.
[0031] In one embodiment of the present application, the fluorine-containing material layer comprises at least one of poly(methyl-3,3,3-trifluoropropylsiloxane) or perfluoropolyether; the carbon material layer comprises at least one of single-walled carbon nanotubes (SWCNT), multi-walled carbon nanotubes (MWCNT) or graphene. The carbon material layer can also be obtained by carbonization of other organic matter, such as tannic acid or polypyrrole. When the fluorine-containing material layer comprises the above-mentioned materials, it is conducive to the formation of a LiF-rich SEI film, further reducing the side reaction of the first silicon-carbon particles with the electrolyte, and effectively inhibiting the expansion of the first silicon-carbon particles, thereby further improving the room temperature cycle performance, low temperature cycle performance and rate performance of the electrochemical device; when the carbon material layer comprises the above-mentioned materials, it can further improve the stability of the SEI film, effectively inhibit the expansion of the second silicon-carbon particles, and can also improve the ionic conductivity of the second silicon-carbon composite material, further improving the kinetic performance of the electrochemical device.
[0032] In the present application, poly(methyl-3,3,3-trifluoropropylsiloxane) may include but is not limited to (C4H7F3OSi) 15 ; Perfluoropolyethers may include but are not limited to (C3F6O) 10 C5F 12 O.
[0033] In one embodiment of the present application, based on the mass of the first silicon-carbon composite material, the mass percentage of fluorine element is 0.05% to 2%. For example, the mass percentage of fluorine element can be 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2% or a range consisting of any two values therein. A fluorine-containing material layer is provided on the surface of the first silicon-carbon particle. When the mass percentage of fluorine element is within the above range, the fluorine-containing material layer has a suitable mass percentage, which is conducive to the formation of a LiF-rich SEI film, further reducing the side reaction of the first silicon-carbon particle with the electrolyte, effectively inhibiting the expansion of the first silicon-carbon particle, and improving the room temperature cycle performance, low temperature cycle performance and rate performance of the electrochemical device.
[0034] In one embodiment of the present application, based on the mass of the first silicon-carbon composite material, the mass percentage W1 of the fluorine-containing material layer is 0.07% to 5.47%. For example, the mass percentage of the fluorine-containing material layer can be 0.07%, 0.1%, 0.5%, 1%, 1.5%, 2%, 3%, 4%, 5%, 5.47% or a range consisting of any two of the values.
[0035] In one embodiment of the present application, based on the mass of the second silicon-carbon composite material, the mass percentage content W2 of the carbon material layer is 0.1% to 0.5%. For example, the mass percentage content of the carbon material layer can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5% or a range consisting of any two of these values.
[0036] In one embodiment of the present application, based on the mass of the first silicon-carbon composite material, the mass percentage of the first silicon-carbon particles is 94.53% to 99.93%; based on the mass of the second silicon-carbon composite material, the mass percentage of the second silicon-carbon particles is 99.5% to 99.9%. For example, the mass percentage of the first silicon-carbon particles can be 94.53%, 95%, 96%, 97%, 98%, 98.5%, 99%, 99.5%, 99.9%, 99.93% or a range consisting of any two of the values; the mass percentage of the second silicon-carbon particles can be 99.5%, 99.6%, 99.7%, 99.8%, 99.9% or a range consisting of any two of the values. When the mass percentage of the first silicon-carbon particles and the mass percentage of the second silicon-carbon particles are within the above range, the electrochemical device of the present application has a higher volumetric energy density, and at the same time has better room temperature cycle performance, low temperature cycle performance and rate performance.
[0037] In one embodiment of the present application, based on the mass of the first silicon-carbon particles, the mass percentage of silicon in the first silicon-carbon particles is 38% to 50%; based on the mass of the second silicon-carbon particles, the mass percentage of silicon in the second silicon-carbon particles is 42% to 60%. For example, the mass percentage of silicon in the first silicon-carbon particles can be 38%, 40%, 42%, 44%, 46%, 48%, 50% or a range consisting of any two of these values; the mass percentage of silicon in the second silicon-carbon particles can be 42%, 45%, 50%, 55%, 60% or a range consisting of any two of these values. When the mass percentage of silicon in the first silicon-carbon particles and the mass percentage of silicon in the second silicon-carbon particles are within the above range, the gram capacity of the first silicon-carbon composite material and the second silicon-carbon composite material can be increased, the volume energy density of the electrochemical device can be increased, and the consumption of the electrolyte during the cycle can be reduced, the room temperature cycle performance and low temperature cycle performance of the electrochemical device can be improved, and the kinetic performance and rate performance of the electrochemical device can also be improved.
[0038] In one embodiment of the present application, based on the mass of the first silicon-carbon particles, the mass percentage of carbon in the first silicon-carbon particles is 50% to 62%; based on the mass of the second silicon-carbon particles, the mass percentage of carbon in the second silicon-carbon particles is 40% to 58%. For example, the mass percentage of carbon in the first silicon-carbon particles can be 50%, 52%, 54%, 56%, 58%, 60%, 62%, or a range consisting of any two of these values; the mass percentage of carbon in the second silicon-carbon particles can be 40%, 45%, 50%, 55%, 58%, or a range consisting of any two of these values.
[0039] In one embodiment of the present application, the compaction density of the negative electrode sheet is 1.6 g / cm 3 Up to 1.8g / cm 3 For example, the compaction density of the negative electrode sheet can be 1.6 g / cm 3 , 1.65g / cm 3 , 1.7g / cm 3 , 1.75g / cm 3 , 1.8g / cm 3 Or a range consisting of any two values. When the compaction density of the negative electrode sheet is within the above range, it is beneficial to improve the kinetic performance of the negative electrode sheet and enhance the energy density of the electrochemical device.
[0040] In one embodiment of the present application, the electrolyte includes sulfolane, and the mass percentage of sulfolane is 0.12% to 0.48% based on the mass of the electrolyte. For example, the mass percentage of sulfolane can be 0.12%, 0.2%, 0.3%, 0.4%, 0.48% or a range consisting of any two of the values. When the electrolyte includes sulfolane, and the mass percentage of sulfolane is within the above range, it is beneficial to generate an inorganic SEI interface rich in sulfur, reduce the energy barrier of desolvation, enhance the interface kinetics, reduce the consumption of electrolyte and active lithium, and improve the room temperature cycle performance and low temperature cycle performance of the electrochemical device.
[0041] In one embodiment of the present application, the electrolyte includes fluoroethylene carbonate (FEC), and the mass percentage of fluoroethylene carbonate is 8% to 20%, preferably 12.5% to 17.5%, based on the mass of the electrolyte. For example, the mass percentage of fluoroethylene carbonate can be 8%, 10%, 12.5%, 15%, 17.5%, 20%, or a range consisting of any two of these values. When the electrolyte includes fluoroethylene carbonate and the mass percentage of fluoroethylene carbonate is within the above range, it can improve the protection of the negative electrode plate, reduce the cycle gas production, and thus improve the room temperature cycle performance and low temperature cycle performance of the electrochemical device.
[0042] In one embodiment of the present application, the negative electrode active material is prepared by the following preparation method: (1) providing a first silicon-carbon particle and a second silicon-carbon particle; (2) taking a fluorine-containing material and a first silicon-carbon particle in a mass ratio of 1:999 to 6:94, adding the fluorine-containing material to anhydrous ethanol, stirring for 0.5h to 1h, adding the first silicon-carbon particle, stirring at room temperature for 3h to 5h, and spray drying to obtain a first silicon-carbon composite material; (3) taking a carbon material and a second silicon-carbon particle in a mass ratio of 2:998 to 1:99, adding the carbon material to water to obtain a carbon material dispersion with a solid content of 2% to 4%, stirring for 0.5h to 1h, adding the second silicon-carbon particle, stirring at room temperature for 3h to 5h, and spray drying to obtain a second silicon-carbon composite material; (4) mixing the obtained first silicon-carbon composite material and the second silicon-carbon composite material in a mass ratio of 1:9 to 1:1 to obtain a negative electrode active material. The first silicon-carbon particle and the second silicon-carbon particle in the present application can be prepared by methods known in the art, or can be purchased through commercial channels. In the present application, there is no particular limitation on the instrument used for stirring, as long as the purpose of the present application can be achieved, for example, it can be a mechanical stirrer; there is no particular limitation on the stirring speed, as long as the purpose of the present application can be achieved, for example, the stirring speed can be 500r / min to 800r / min; there is no particular limitation on the spray drying temperature, as long as the purpose of the present application can be achieved, for example, the spray drying temperature can be 180°C to 220°C.
[0043] The present application has no particular restrictions on the method for controlling the mass percentage of silicon in the first silicon-carbon particles and the second silicon-carbon particles, as long as the purpose of the present application can be achieved. For example, the mass percentage of silicon in the first silicon-carbon particles and the second silicon-carbon particles can be controlled by controlling the flow rate of the silicon-based gas passing through the porous carbon material, the deposition time of silicon on the porous carbon material, the temperature of silicon on the porous carbon material, and the like.
[0044] The present application does not particularly limit the regulation method of the average particle size of the first silicon-carbon composite material and the second silicon-carbon composite material, as long as the purpose of the present application can be achieved. Exemplarily, the average particle size of the first silicon-carbon particles and the second silicon-carbon particles can be regulated to correspond to the average particle size of the first silicon-carbon composite material and the second silicon-carbon composite material. In the present application, the average particle size of the first silicon-carbon particles and the second silicon-carbon particles can be regulated by grinding the first silicon-carbon particles and the second silicon-carbon particles. For example, the average particle size of the first silicon-carbon particles and the second silicon-carbon particles can be regulated by regulating the grinding time and the grinding speed. When other conditions remain unchanged, the grinding time is extended, the average particle size of the first silicon-carbon particles and the second silicon-carbon particles decreases, and the average particle size of the first silicon-carbon composite material and the second silicon-carbon composite material decreases; the grinding time is shortened, the average particle size of the first silicon-carbon particles and the second silicon-carbon particles increases, and the average particle size of the first silicon-carbon composite material and the second silicon-carbon composite material increases.
[0045] The present application has no particular restrictions on the regulation method of N1 and N1 / (N1+N2), as long as the purpose of the present application can be achieved. For example, N1 and N1 / (N1+N2) can be regulated by regulating the mass ratio of the first silicon-carbon composite material and the second silicon-carbon composite material during the preparation of the negative electrode active material. When the mass ratio of the first silicon-carbon composite material and the second silicon-carbon composite material increases, N1 and N1 / (N1+N2) increase; when the mass ratio of the first silicon-carbon composite material and the second silicon-carbon composite material decreases, N1 and N1 / (N1+N2) decrease.
[0046] In the present application, the average thickness D1 of the fluorine-containing material layer can be regulated by regulating the mass ratio of the first silicon-carbon particles and the fluorine-containing material. For example, when the mass ratio of the first silicon-carbon particles and the fluorine-containing material increases, the average thickness D1 of the fluorine-containing material layer decreases; when the mass ratio of the first silicon-carbon particles and the fluorine-containing material decreases, the average thickness D1 of the fluorine-containing material layer increases.
[0047] In the present application, the average thickness D2 of the carbon material layer can be regulated by regulating the mass ratio of the second silicon-carbon particles and the carbon material. For example, when the mass ratio of the second silicon-carbon particles and the carbon material increases, the average thickness D2 of the carbon material layer decreases; when the mass ratio of the second silicon-carbon particles and the carbon material decreases, the average thickness D2 of the carbon material layer increases.
[0048] In the present application, the mass percentage of fluorine element can be regulated by regulating the mass ratio of the first silicon-carbon particles and the fluorine-containing material. For example, when the mass ratio of the first silicon-carbon particles and the fluorine-containing material increases, the mass percentage of fluorine element decreases; when the mass ratio of the first silicon-carbon particles and the fluorine-containing material decreases, the mass percentage of fluorine element increases.
[0049] In the present application, the compaction density of the negative electrode sheet can be adjusted by adjusting the rolling pressure of the cold pressing process. For example, when the rolling pressure of the cold pressing process increases, the compaction density of the negative electrode sheet increases; when the rolling pressure of the cold pressing process decreases, the compaction density of the negative electrode sheet decreases.
[0050] In the present application, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or can be disposed on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the negative electrode current collector, or it can be a partial area of the surface of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.
[0051] The present application has no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper, lithium-copper composite current collector, carbon-copper composite current collector, nickel-copper composite current collector or titanium-copper composite current collector, etc.
[0052] In the present application, the negative electrode active material also includes at least one of artificial graphite, natural graphite, mesophase micro carbon spheres, hard carbon or soft carbon. In some embodiments of the present application, the negative electrode material layer may also include a conductive agent and a binder. The present application does not particularly limit the types of conductive agents and binders, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to conductive carbon black, carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers. At least one of the above-mentioned conductive carbon black may include but is not limited to Super P, acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nanocarbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymer may include but is not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. The binder may include, but is not limited to, at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamideimide, polyvinylidene fluoride, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin or nylon.
[0053] The present application has no particular restriction on the mass ratio of the negative electrode active material, the conductive agent, and the binder in the negative electrode material layer. Those skilled in the art can select the ratio according to actual needs as long as the purpose of the present application can be achieved.
[0054] In some embodiments of the present application, the negative electrode material layer may also include a conductive agent, a binder and a thickener. The present application does not particularly limit the types of the conductive agent, binder and thickener, as long as the purpose of the present application can be achieved. For example, the conductive agent and the binder may be at least one of the aforementioned conductive agent and the aforementioned binder. The thickener may include but is not limited to at least one of carboxymethyl cellulose, sodium carboxymethyl cellulose or lithium carboxymethyl cellulose. The present application does not particularly limit the mass ratio of the negative electrode active material, conductive agent, binder and thickener in the negative electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.
[0055] The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the single-sided negative electrode material layer is 30 μm to 120 μm.
[0056] The present application has no particular limitation on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 15 μm.
[0057] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. For example, the conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be, for example, at least one of the aforementioned conductive agent and the aforementioned binder.
[0058] In the present application, the electrochemical device includes a positive electrode plate, and the positive electrode plate includes a positive electrode collector and a positive electrode material layer disposed on at least one surface of the positive electrode collector. The above-mentioned "positive electrode material layer disposed on at least one surface of the positive electrode collector" means that the positive electrode material layer can be disposed on one surface of the positive electrode collector along its own thickness direction, or it can be disposed on two surfaces of the positive electrode collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the positive electrode collector, or it can be a partial area of the surface of the positive electrode collector. This application has no special restrictions, as long as the purpose of this application can be achieved.
[0059] The present application has no particular restrictions on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, a metal foil or a composite current collector can be used. For example, the metal foil may include but is not limited to aluminum foil; the composite current collector may be obtained by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate.
[0060] In the present application, the positive electrode material layer includes a positive electrode active material. The present application has no particular limitation on the positive electrode active material as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate, lithium titanate, lithium nickel manganese aluminum oxide, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium iron silicate, lithium vanadium silicate, lithium cobalt silicate, lithium manganese silicate or at least one of spinel-type lithium nickel manganese oxide.
[0061] In the present application, the positive electrode material layer may also include a conductive agent and a binder. The present application does not particularly limit the types of the conductive agent and the binder, as long as the purpose of the present application can be achieved. For example, it may be at least one of the aforementioned conductive agent and the aforementioned binder. The present application does not particularly limit the mass ratio of the positive electrode active material, the conductive agent, and the binder in the positive electrode material layer. Those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.
[0062] The present application has no particular restrictions on the thickness of the positive electrode current collector and the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm, and the thickness of the single-sided positive electrode material layer is 30 μm to 150 μm.
[0063] Optionally, the positive electrode sheet may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The composition of the conductive layer is not particularly limited, and it can be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application does not particularly limit the conductive agent and the binder in the conductive layer, for example, it can be at least one of the aforementioned conductive agent and the aforementioned binder.
[0064] In the present application, the electrochemical device also includes an isolation membrane. The present application has no particular restrictions on the isolation membrane, as long as the purpose of the present application can be achieved. For example, the material of the isolation membrane may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of isolation membrane may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.
[0065] In some embodiments of the present application, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.
[0066] Optionally, a surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer can be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. In some embodiments of the present application, the inorganic layer includes inorganic particles and a binder. The present application has no particular restrictions on inorganic particles, for example, inorganic particles can include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the binder, for example, the binder can be at least one of the aforementioned binders. In some embodiments of the present application, the polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).
[0067] In the present application, the thickness of the isolation film is not particularly limited as long as the purpose of the present application can be achieved. For example, the thickness of the isolation film may be 3 μm to 30 μm.
[0068] In the present application, the electrolyte includes a lithium salt and a non-aqueous solvent. The present application has no particular restrictions on the lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalatoborate) (LiBOB) or lithium difluoroborate. The present application has no particular restrictions on the mass percentage of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the mass of the electrolyte, the mass percentage of the lithium salt can be 8% to 20%.
[0069] The present application has no particular restrictions on non-aqueous solvents, as long as the purpose of the present application can be achieved, for example, non-aqueous solvents may include but are not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of linear carbonate compounds, cyclic carbonate compounds or fluorinated carbonate compounds. The above-mentioned linear carbonate compounds may include but are not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (MEC). The above-mentioned cyclic carbonate compounds may include but are not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application has no particular restriction on the mass percentage of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the mass of the electrolyte, the mass percentage of the non-aqueous solvent can be 59.52% to 92%.
[0070] In one embodiment of the present application, the electrolyte may include a lithium salt and a non-aqueous solvent, the mass percentage of the lithium salt is as described above, and the mass percentage of the non-aqueous solvent is 80% to 92%. The electrochemical device including the above electrolyte has good low-temperature cycle performance and rate performance.
[0071] In one embodiment of the present application, the electrolyte may include sulfolane, lithium salt and non-aqueous solvent, the mass percentage of sulfolane and lithium salt is as described above, and the mass percentage of non-aqueous solvent is 79.52% to 91.88%. The electrochemical device including the above electrolyte has good low temperature cycle performance and rate performance.
[0072] In one embodiment of the present application, the electrolyte may include fluoroethylene carbonate, lithium salt and non-aqueous solvent, the mass percentage of fluoroethylene carbonate and lithium salt is as described above, and the mass percentage of non-aqueous solvent is 60% to 84%. The electrochemical device including the above electrolyte has good low temperature cycle performance and rate performance.
[0073] In one embodiment of the present application, the electrolyte may include fluoroethylene carbonate, sulfolane, lithium salt and non-aqueous solvent, the mass percentage of fluoroethylene carbonate, sulfolane and lithium salt is as described above, and the mass percentage of non-aqueous solvent is 59.52% to 83.88%. The electrochemical device including the above electrolyte has good low temperature cycle performance and rate performance.
[0074] In the present application, the electrochemical device also includes a shell for accommodating a positive electrode plate, a separator, a negative electrode plate and an electrolyte, as well as other components known in the field of electrochemistry, and the present application does not limit the above-mentioned other components. The present application has no special restrictions on the shell, and it can be a shell known in the art, as long as the purpose of the present application can be achieved. For example, the shell can be a hard shell or a flexible shell. The material of the hard shell can be metal, and the present application does not limit the type of metal, and a metal hard shell known in the art can be used, as long as the purpose of the present application can be achieved. The flexible shell can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0075] The present application does not particularly limit the type of electrochemical device, which may include any device that undergoes an electrochemical reaction. In the present application, the electrochemical device may include, but is not limited to: a lithium metal electrochemical device, a lithium ion electrochemical device (lithium ion battery), a lithium polymer electrochemical device or a lithium ion polymer electrochemical device (lithium ion polymer battery), etc.
[0076] The preparation process of the electrochemical device of the present application is well known to those skilled in the art, and the present application has no particular limitations. For example, the preparation process of the electrochemical device may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly with a wound structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. Alternatively, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly with a stacked structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.
[0077] The second aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. The electronic device of the present application has good low-temperature cycle performance and rate performance.
[0078] The present application does not particularly limit the type of electronic device, and it can be used for any electronic device known in the prior art. In some embodiments of the present application, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0079] Example
[0080] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0081] Silicon mass percentage test
[0082] The negative electrode sheet was plasma cut longitudinally along the thickness direction, polished by argon ion polishing technology to obtain a flat cross section, and the obtained cross section was tested using an X-ray energy spectrometer (EDS) equipped with a scanning electron microscope of model OXFORD·EDS at an acceleration voltage of 10kV and an emission current of 10mA. 10 first silicon-carbon particles and second silicon-carbon particles were selected for surface scanning to test the mass percentage of silicon element, and the average value was calculated to obtain the mass percentage of silicon element W in the first silicon-carbon particles. S1 and the mass percentage content W of silicon in the second silicon-carbon particle S2 .
[0083] Scanning electron microscope test
[0084] The negative electrode sheet was plasma cut longitudinally along the thickness direction and polished by argon ion polishing technology to obtain a flat cross section. The cross section of the negative electrode sheet was observed using a scanning electron microscope. The selected test instrument was: OXFORD·EDS. The magnification was adjusted to 500 times, and a counting area of 160μm×120μm in the cross section of the negative electrode sheet was observed.
[0085] In the scanning electron microscope image, 10 first silicon-carbon composite material particles are randomly selected and their particle sizes are measured, and the average value is calculated to obtain the average particle size P1 of the first silicon-carbon composite material.
[0086] In the scanning electron microscope image, 10 particles of the second silicon-carbon composite material are randomly selected and the particle sizes are measured, and the average value is calculated to obtain the average particle size P2 of the second silicon-carbon composite material.
[0087] In the counting area, the first silicon-carbon composite material is counted to obtain N1 particles of the first silicon-carbon composite material; and the second silicon-carbon composite material is counted to obtain N2 particles of the second silicon-carbon composite material, and N1 / (N1+N2) is obtained by calculation.
[0088] Average thickness test of carbon material layer and fluorine-containing material layer
[0089] A transmission electron microscope (model: JEM-120i) was used to observe and measure the thickness of the fluorine-containing material layer on the surface of the first silicon-carbon particle. The thickness of the fluorine-containing material layer at three positions was measured and the average value was taken to obtain the average thickness D1 of the fluorine-containing material layer. The thickness of the carbon material layer on the surface of the second silicon-carbon particle was observed and measured. The thickness of the carbon material layer at three positions was measured and the average value was taken to obtain the average thickness D2 of the carbon material layer.
[0090] Fluorine element mass percentage test
[0091] The negative electrode sheet is plasma cut longitudinally along the thickness direction, polished by argon ion polishing technology to obtain a flat cross section, and the cross section of the negative electrode sheet is observed by using a scanning electron microscope (model OXFORD·EDS), and the mass percentage content of the fluorine element in the first silicon-carbon composite material is tested by using an X-ray energy spectrometer (EDS) equipped with the scanning electron microscope under the conditions of an acceleration voltage of 10 kV and an emission current of 10 mA to obtain the mass percentage content of the fluorine element in the first silicon-carbon composite material W. F .
[0092] Compaction density test of negative electrode
[0093] After the lithium-ion battery is charged to 4.35V at 0.1C, it is discharged to 3.0V at 0.1C, and the discharge capacity is recorded as C1. Then the lithium-ion battery is charged to C1 / 2 at 0.1C, at which time the lithium-ion battery is half-charged. The lithium-ion battery is disassembled to obtain the negative electrode sheet in the half-charged state. The negative electrode sheet is cleaned with dimethyl carbonate DMC and vacuum dried, and the area is cut to S cm 2 The negative electrode sheet is measured to have a thickness of H cm and a mass of Mg. The compaction density of the negative electrode sheet can be calculated to be A = M / (S×H), in g / cm 3 .
[0094] Preparation of button half-cell
[0095] (1) The first silicon-carbon composite material, acetylene black and sodium alginate are added to deionized water in a mass ratio of 80:10:10, and stirred thoroughly to form a slurry with a solid content of 40 wt%. The slurry is applied on a copper foil of 8 μm thickness with a doctor blade to form a coating of 100 μm thickness, and dried in a vacuum drying oven at 85°C for 12 hours, and then cut into discs with a diameter of 1 cm by a punch in a dry environment to obtain a positive electrode. In an argon atmosphere glove box with a water content of less than 10 ppm, ethylene carbonate (EC) and dimethyl carbonate (DMC) are mixed in a mass ratio of 1:1 to obtain a mixed solution, and LiPF6 and fluoroethylene carbonate are added to the mixed solution and stirred to obtain an electrolyte, wherein, based on the total mass of the electrolyte, the mass percentage of fluoroethylene carbonate is 15.5%, the mass percentage of LiPF6 is 12.5%, and the remainder is the mixed solution. A Celgard2400 isolation membrane with a thickness of 9 μm is used. A lithium metal sheet is used as the counter electrode of the positive electrode. The positive electrode, the separator, and the lithium metal sheet are stacked in order, and the electrolyte is added to assemble the button-type half-cell Cell1 in a glove box.
[0096] (2) The second silicon-carbon composite material, acetylene black and sodium alginate were added to deionized water in a mass ratio of 80:10:10, and stirred thoroughly to form a slurry with a solid content of 40 wt%. The slurry was coated on a copper foil of 8 μm thickness with a scraper to form a coating of 100 μm thickness, and dried in a vacuum drying oven at 85°C for 12 hours, and then cut into discs with a diameter of 1 cm by a punch in a dry environment to obtain a positive electrode. In an argon atmosphere glove box with a water content of less than 10 ppm, ethylene carbonate (EC) and dimethyl carbonate (DMC) were mixed in a mass ratio of 1:1 to obtain a mixed solution, and LiPF6 and fluoroethylene carbonate were added to the mixed solution and stirred to obtain an electrolyte, wherein, based on the total mass of the electrolyte, the mass percentage of fluoroethylene carbonate was 15.5%, the mass percentage of LiPF6 was 12.5%, and the remainder was the mixed solution. A Celgard2400 isolation membrane with a thickness of 9 μm was used. A lithium metal sheet is used as the counter electrode of the positive electrode. The positive electrode, the separator, and the lithium metal sheet are stacked in order, and the electrolyte is added to assemble the button-type half-cell Cell2 in a glove box.
[0097] First cycle charge and discharge efficiency test
[0098] At 25°C and normal pressure, the prepared button half-cell was discharged to 0.01V at a rate of 0.05C, left to stand for 5 minutes, then discharged to 0.01V at a constant current of 50μA, and then discharged to 0.01V at a constant current of 10μA, and the discharge capacity at this time was recorded; then left to stand for 5 minutes, and then charged to 2.0V at a rate of 0.05C, and the charge capacity at this time was recorded. First cycle charge and discharge efficiency (%) = charge capacity / discharge capacity × 100%.
[0099] The first cycle charge and discharge efficiency of the tested button-type half-cell Cell1 is the first cycle charge and discharge efficiency of the first silicon-carbon composite material; the first cycle charge and discharge efficiency of the tested button-type half-cell Cell2 is the first cycle charge and discharge efficiency of the second silicon-carbon composite material.
[0100] Room temperature cycle performance test
[0101] The test temperature is 25°C. The lithium-ion battery is charged to 4.35V at a constant current of 0.7C, and then charged to 0.025C at a constant voltage of 4.35V. After standing for 5 minutes, it is discharged to 3.0V at a constant current of 0.5C. The discharge capacity obtained in this step is the initial capacity. Carry out charging and discharging cycle tests according to the above steps, and make a ratio of the discharge capacity of each step to the initial capacity to obtain the discharge capacity retention rate of each step, and record the number of cycles of the lithium-ion battery at 25°C until the discharge capacity retention rate is 90%. The room temperature cycle performance of the lithium-ion battery is characterized by the number of cycles at 25°C until the capacity retention rate is 90%. The higher the number of cycles of the lithium-ion battery at 25°C until the capacity retention rate is 90%, the better the room temperature cycle performance of the lithium-ion battery.
[0102] Rate performance test
[0103] At 25°C, discharge the lithium-ion battery at a constant current of 0.2C to 3.0V and let it stand for 5 minutes; charge at a constant current of 0.5C to 4.35V, charge at a constant voltage of 4.35V to 0.05C, let it stand for 5 minutes, discharge at a constant current of 0.2C to 3.0V, and record the discharge capacity at this time as C0, and let it stand for 5 minutes; charge at a constant current of 0.5C to 4.35V, charge at a constant voltage of 4.35V to 0.05C, let it stand for 5 minutes, and discharge at a constant current of 2C to 3.0V, and record the discharge capacity at this time as C2.
[0104] Capacity retention rate at 2C (%) = C2 / C0×100%.
[0105] The ratio of the discharge capacity of a lithium-ion battery at 2C to 0.2C, C2 / C0, is used to characterize the rate performance of the lithium-ion battery. The larger the ratio of the discharge capacity at 2C to 0.2C, C2 / C0, the better the rate performance of the lithium-ion battery.
[0106] Low temperature cycle performance test
[0107] Place the lithium-ion battery in a -10℃ constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature to 4.35V at a constant current of 0.2C at -10℃, charge it to 0.05C at a constant voltage at 4.35V, let it stand for 5 minutes, and then discharge it to 3.0V at a constant current of 0.2C, let it stand for 5 minutes, and record the discharge capacity at this time as the initial capacity C3. This is a charge and discharge cycle. Cycle 200 times according to the above charging and discharging cycle steps, measure the discharge capacity C4 of the lithium-ion battery after 200 cycles, and calculate the capacity retention rate of the lithium-ion battery after 200 cycles.
[0108] The capacity retention rate after 200 cycles at -10°C (%) = C4 / C3×100%.
[0109] The capacity retention rate of a lithium-ion battery after 200 cycles is used to characterize the low-temperature cycle performance of the lithium-ion battery. The higher the capacity retention rate of the lithium-ion battery after 200 cycles at -10°C, the better the low-temperature cycle performance of the lithium-ion battery.
[0110] Example 1-1
[0111] <Preparation of negative electrode active material>
[0112] (1) 6 g of fluorine-containing material poly (methyl-3,3,3-trifluoropropylsiloxane) was added dropwise into 1000 mL of anhydrous ethanol, stirred for 0.5 h, and then 200 g of the first silicon-carbon particles were added, stirred at room temperature for 4 h, and spray-dried to obtain a first silicon-carbon composite material. The average particle size P1 of the first silicon-carbon composite material is 3 μm, the average thickness D1 of the fluorine-containing material layer is 17.7 nm, and the mass percentage of silicon element in the first silicon-carbon particles is W. S1 is 45.2%; the stirring speed is 600r / min; the spray drying temperature is 200℃.
[0113] (2) 1 g of carbon material single-walled carbon nanotube (SWCNT) was added to water to obtain a carbon material dispersion with a solid content of 3%, and after stirring for 0.5 h, 200 g of the second silicon-carbon particles were added, and the mixture was stirred at room temperature for 4 h, and then spray-dried to obtain a second silicon-carbon composite material. The average particle size P2 of the second silicon-carbon composite material was 9 μm, the average thickness D2 of the carbon material layer was 11.5 nm, and the mass percentage of silicon element in the second silicon-carbon particles was W. S2 is 52.3%; the stirring speed is 700r / min; the spray drying temperature is 200℃.
[0114] (3) The artificial graphite, the first silicon-carbon composite material, and the second silicon-carbon composite material are uniformly mixed in a mass ratio of 90:3:7 to obtain a negative electrode active material.
[0115] <Preparation of negative electrode sheet>
[0116] The negative electrode active material prepared above, the binder styrene butadiene rubber (SBR), and the thickener carboxymethyl cellulose (CMC) were mixed in a mass ratio of 98:1.6:0.4, dissolved in deionized water as a negative electrode solvent, and mixed evenly to prepare a negative electrode slurry with a solid content of 45wt%. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried at 85℃ for 4h to obtain a negative electrode sheet with a single-sided coating of a negative electrode material layer. The coating weight of the negative electrode material layer was 142mg / 1540mm 2Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a negative electrode material layer coated on both sides. After cold pressing, cutting and slitting, it is dried under vacuum conditions at 120°C for 12 hours to obtain a negative electrode sheet with a specification of 76.6mm×875mm for standby use. Among them, the compaction density of the negative electrode sheet is 1.7g / cm 3 .
[0117] <Preparation of positive electrode sheet>
[0118] The positive electrode active material, lithium nickel cobalt manganese oxide (NCM811), the conductive agent, acetylene black, and the binder, polyvinylidene fluoride (PVDF), were mixed in a mass ratio of 96.3:2.2:1.5, and the positive electrode solvent, N-methylpyrrolidone, was added and stirred evenly to obtain a positive electrode slurry with a solid content of 75wt%. The positive electrode slurry was evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 13μm, and dried at 85°C to obtain a positive electrode sheet with a single-sided coating of a positive electrode material layer, and the coating weight of the positive electrode material layer was 267.8mg / 1540mm 2 Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided positive electrode material layer. After cold pressing, cutting, and slitting, it is dried under vacuum conditions at 85°C for 4 hours to obtain a positive electrode sheet with a specification of 74mm×867mm for standby use. Among them, the cold pressing pressure is 20T, and the compaction density of the positive electrode sheet is 4.15g / cm 3 .
[0119] <Preparation of Electrolyte>
[0120] In an argon atmosphere glove box with a water content of less than 10ppm, ethylene carbonate (EC) and dimethyl carbonate (DMC) are mixed uniformly in a mass ratio of 1:1 to obtain a base solvent, and fluoroethylene carbonate and LiPF6 are added to the base solvent and stirred uniformly to obtain an electrolyte. Wherein, based on the total mass of the electrolyte, the mass percentage of fluoroethylene carbonate is 15.5%, the mass percentage of LiPF6 is 12.5%, and the mass percentage of the base solvent is 72%.
[0121] <Isolation film>
[0122] A polyethylene (PE) porous membrane with a thickness of 9 μm was used as the separator.
[0123] <Preparation of lithium-ion batteries>
[0124] The positive electrode sheet after welding the pole ear, the separator, and the negative electrode sheet after welding the pole ear are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain the electrode assembly. The electrode assembly is placed in an aluminum plastic film, placed in a vacuum oven at 80°C for 12 hours to remove moisture, and the above-prepared electrolyte is injected. After vacuum packaging, standing, formation (charging to 3.5V at a constant current of 0.02C, and then charging to 3.9V at a constant current of 0.1C), degassing, and trimming process flow, a lithium-ion battery is obtained.
[0125] Example 1-2 to Example 1-8
[0126] The above method is the same as Example 1-1 except that the average particle sizes of the first silicon-carbon particles and the second silicon-carbon particles are adjusted in <Preparation of Negative Electrode Active Material> so that the average particle sizes of the first silicon-carbon composite material and the second silicon-carbon composite material are as shown in Table 1.
[0127] Example 1-9 to Example 1-12
[0128] Except that the mass ratio of the first silicon-carbon composite material to the second silicon-carbon composite material is adjusted in <Preparation of Negative Electrode Active Material> so that the values of N1 and N1 / (N1+N2) are as shown in Table 2, the rest is the same as Example 1-1.
[0129] Example 1-13 to Example 1-16
[0130] Except that the mass ratio of the first silicon-carbon particles and the fluorine-containing material is adjusted in <Preparation of Negative Electrode Active Material> so that the average thickness D1 of the fluorine-containing material layer is as shown in Table 1, the rest is the same as Example 1-1.
[0131] Example 1-17 to Example 1-20
[0132] Except that the mass ratio of the second silicon-carbon particles and the carbon material was adjusted in <Preparation of Negative Electrode Active Material> so that the average thickness D2 of the carbon material layer was as shown in Table 1, the rest was the same as Example 1-1.
[0133] Example 1-21 to Example 1-26
[0134] Except that the relevant preparation parameters in <Preparation of Negative Electrode Active Material> were adjusted according to Table 1, the rest was the same as Example 1-1.
[0135] Examples 1-27
[0136] The process was the same as Example 1-1 except that 0.5 g of single-walled carbon nanotubes and 0.5 g of multi-walled carbon nanotubes were mixed as the carbon material in <Preparation of Negative Electrode Active Material>.
[0137] Example 1-28 to Example 1-29
[0138] Except that the rolling pressure in the cold pressing process is adjusted in <Preparation of Negative Electrode Sheet> so that the compaction density of the negative electrode sheet is as shown in Table 2, the rest is the same as Example 1-1.
[0139] Example 2-1 to Example 2-5
[0140] Except that sulfolane is further added in <Preparation of Electrolyte> and relevant preparation parameters are adjusted according to Table 3, the rest is the same as Example 1-1. Among them, when the mass percentage of sulfolane changes, the mass percentage of the base solvent changes accordingly, and the mass ratio of each component of the base solvent, the mass percentage of the lithium salt and the mass percentage of fluoroethylene carbonate remain unchanged.
[0141] Example 2-6 to Example 2-11
[0142] Except for adjusting the mass percentage of FEC in <Preparation of Electrolyte> according to Table 3, the rest is the same as Example 1-1. When the mass percentage of FEC changes, the mass percentage of the base solvent changes accordingly, and the mass ratio of each component of the base solvent and the mass percentage of the lithium salt remain unchanged.
[0143] Comparative Example 1
[0144] Except that the first silicon-carbon particles are directly used as the negative electrode active material in <Preparation of Negative Electrode Active Material>, the rest is the same as Example 1-1.
[0145] Comparative Example 2
[0146] Except that the second silicon-carbon particles are directly used as the negative electrode active material in <Preparation of Negative Electrode Active Material>, the rest is the same as Example 1-1.
[0147] Comparative Example 3
[0148] Except that the first silicon-carbon composite material is directly used as the negative electrode active material in <Preparation of Negative Electrode Active Material>, the rest is the same as Example 1-1.
[0149] Comparative Example 4
[0150] Except that the second silicon-carbon composite material is directly used as the negative electrode active material in <Preparation of Negative Electrode Active Material>, the rest is the same as Example 1-1.
[0151] Comparative Example 5
[0152] The process was the same as Example 1-1 except that the carbon material layer was not provided on the surface of the second silicon-carbon particles in <Preparation of Negative Electrode Active Material>.
[0153] Comparative Example 6
[0154] Except that the fluorine-containing material layer is not provided on the surface of the first silicon-carbon particles in <Preparation of Negative Electrode Active Material>, the rest is the same as Example 1-1.
[0155] Comparative Examples 7 to 9
[0156] The above method is the same as Example 1-1 except that the average particle sizes of the first silicon-carbon particles and the second silicon-carbon particles are adjusted in <Preparation of Negative Electrode Active Material> so that the average particle sizes of the first silicon-carbon composite material and the second silicon-carbon composite material are as shown in Table 1.
[0157] The preparation parameters and performance tests of various embodiments and comparative examples are shown in Table 1, Table 2 and Table 3.
[0158]
[0159]
[0160]
[0161]
[0162] It can be seen from Examples 1-1 to 1-29 and Comparative Examples 1 to 9 that a fluorine-containing material layer and a carbon material layer are respectively provided on the surfaces of the first silicon-carbon particles and the second silicon-carbon particles, and the obtained first silicon-carbon composite material and the second silicon-carbon composite material have higher first-cycle charge and discharge efficiency, and after the first silicon-carbon composite material and the second silicon-carbon composite material are mixed in proportion, when the average particle size of the first silicon-carbon composite material and the average particle size of the second silicon-carbon composite material are within the range of the present application, the obtained lithium-ion battery has a higher capacity retention rate after 200 cycles at -10°C, a higher number of cycles at 25°C until the capacity retention rate is 90%, and a higher capacity retention rate at 2C, indicating that the low-temperature cycle performance, room-temperature cycle performance and rate performance of the lithium-ion battery of the present application are improved. The negative electrode active materials of Comparative Examples 1 to 6 are not within the scope of the present application, and the average particle size of the first silicon-carbon composite material and the average particle size of the second silicon-carbon composite material in Comparative Examples 7 to 9 are not within the scope of the present application. The lithium-ion batteries obtained in the above comparative examples have a low capacity retention rate after 200 cycles at -10°C, a low number of cycles at 25°C until the capacity retention rate is 90%, and a low capacity retention rate at 2C, indicating that the low-temperature cycle performance, room temperature cycle performance and rate performance of the lithium-ion batteries in Comparative Examples 1 to 9 are poor.
[0163] The values of N1 and N1 / (N1+N2) usually affect the room temperature cycle performance and low temperature cycle performance of lithium-ion batteries. It can be seen from Examples 1-1, 1-9 to 1-12 that when the values of N1 and N1 / (N1+N2) are within the scope of this application, the capacity retention rate of the obtained lithium-ion battery after 200 cycles at -10°C is high, the number of cycles at 25°C until the capacity retention rate is 90% is high, and the capacity retention rate at 2C is high, indicating that the room temperature cycle performance and low temperature cycle performance of the lithium-ion battery of this application are improved, and it also has good rate performance.
[0164] The average thickness D1 of the fluorine-containing material layer usually affects the room temperature cycle performance, low temperature cycle performance and rate performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-13 to 1-16 that when the average thickness D1 of the fluorine-containing material layer is within the range of the present application, the obtained lithium-ion battery has a high capacity retention rate after 200 cycles at -10°C, a high number of cycles at 25°C until the capacity retention rate is 90%, and a high capacity retention rate at 2C, indicating that the room temperature cycle performance, low temperature cycle performance and rate performance of the lithium-ion battery of the present application are improved.
[0165] The average thickness D2 of the carbon material layer usually affects the room temperature cycle performance and low temperature cycle performance of the lithium ion battery. It can be seen from Examples 1-1, 1-17 to 1-20 that when the average thickness D2 of the carbon material layer is within the scope of the present application, the obtained lithium ion battery has a high capacity retention rate after 200 cycles at -10°C, a high number of cycles at 25°C until the capacity retention rate is 90%, and a high capacity retention rate at 2C, indicating that the room temperature cycle performance and low temperature cycle performance of the lithium ion battery of the present application are improved, and it also has good rate performance.
[0166] The mass percentage of silicon in the first silicon-carbon particles and the mass percentage of silicon in the second silicon-carbon particles usually affect the room temperature cycle performance, low temperature cycle performance and rate performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-21 to 1-24 that when the mass percentage of silicon in the first silicon-carbon particles and the mass percentage of silicon in the second silicon-carbon particles are within the scope of the present application, the obtained lithium-ion battery has a high capacity retention rate after 200 cycles at -10°C, a high number of cycles at 25°C until the capacity retention rate is 90%, and a high capacity retention rate at 2C, indicating that the room temperature cycle performance, low temperature cycle performance and rate performance of the lithium-ion battery of the present application are improved.
[0167] The type of fluorine-containing material layer and the type of carbon material layer usually affect the room temperature cycle performance, low temperature cycle performance and rate performance of lithium-ion batteries. It can be seen from Examples 1-1, 1-25 to 1-27 that when the type of fluorine-containing material layer and the type of carbon material layer are within the scope of this application, the obtained lithium-ion battery has a high capacity retention rate after 200 cycles at -10°C, a high number of cycles at 25°C until the capacity retention rate is 90%, and a high capacity retention rate at 2C, indicating that the room temperature cycle performance, low temperature cycle performance and rate performance of the lithium-ion battery of this application are improved.
[0168] It can be seen from Example 1-1, Example 1-28 to Example 1-29 that when the compaction density of the negative electrode plate is within the range of the present application, the obtained lithium-ion battery has a high number of cycles at 25°C with a capacity retention rate of 90%, a low thickness expansion rate after storage at 80°C for 24 hours, and a high capacity retention rate at 2C, indicating that the lithium-ion battery of the present application has good room temperature cycle performance, low temperature cycle performance and rate performance.
[0169] Table 3
[0170]
[0171] Note: “ / ” in Table 3 indicates that there is no corresponding preparation parameter or substance.
[0172] The mass percentage of sulfolane usually affects the low-temperature cycle performance and room-temperature cycle performance of lithium-ion batteries. It can be seen from Examples 1-1, 2-1 to 2-5 that when the mass percentage of sulfolane is within the range of this application, the obtained lithium-ion battery has a high capacity retention rate after 200 cycles at -10°C, a high number of cycles at 25°C until the capacity retention rate is 90%, and a high capacity retention rate at 2C, indicating that the low-temperature cycle performance and room-temperature cycle performance of the lithium-ion battery of this application are improved, and at the same time have good rate performance.
[0173] The mass percentage of fluoroethylene carbonate usually affects the low-temperature cycle performance and room-temperature cycle performance of lithium-ion batteries. It can be seen from Examples 1-1, 2-6 to 2-11 that when the mass percentage of fluoroethylene carbonate is within the range of the present application, the obtained lithium-ion battery has a high capacity retention rate after 200 cycles at -10°C, a high number of cycles at 25°C until the capacity retention rate is 90%, and a high capacity retention rate at 2C, indicating that the low-temperature cycle performance and room-temperature cycle performance of the lithium-ion battery of the present application are improved, and at the same time have good rate performance.
[0174] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.
[0175] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0176] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. An electrochemical device, comprising an electrolyte and a negative electrode plate, wherein the negative electrode plate comprises a negative electrode material layer, wherein the negative electrode material layer comprises a first silicon-carbon composite material and a second silicon-carbon composite material, wherein the first silicon-carbon composite material comprises first silicon-carbon particles and a fluorine-containing material layer located on the surface of the first silicon-carbon particles, and the second silicon-carbon composite material comprises second silicon-carbon particles and a carbon material layer located on the surface of the second silicon-carbon particles; wherein the average particle size of the first silicon-carbon composite material is 2 μm to 6 μm, and the average particle size of the second silicon-carbon composite material is 7 μm to 20 μm.
2. The electrochemical device according to claim 1, wherein: The average particle size of the first silicon-carbon composite material is 2 μm to 4 μm, and the average particle size of the second silicon-carbon composite material is 7 μm to 11 μm.
3. The electrochemical device according to claim 1, wherein The cross section of the negative electrode sheet includes a counting area, and the area of the counting area is 19200 μm 2 , in the counting area, the number of particles of the first silicon-carbon composite material is N1, and 20≤N1≤100.
4. The electrochemical device according to claim 1, wherein The number of particles of the first silicon-carbon composite material is N1, the number of particles of the second silicon-carbon composite material is N2, and 0.18≤N1 / (N1+N2)≤0.
67.
5. The electrochemical device according to claim 1, wherein The average thickness D1 of the fluorine-containing material layer is 10 nm to 25 nm, preferably 14 nm to 21.2 nm.
6. The electrochemical device according to claim 1, wherein The average thickness D2 of the carbon material layer is 8.4 nm to 13.7 nm, preferably 9.5 nm to 12.6 nm.
7. The electrochemical device according to claim 1, wherein: The fluorine-containing material layer comprises at least one of poly(methyl-3,3,3-trifluoropropylsiloxane) or perfluoropolyether; and the carbon material layer comprises at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes or graphene.
8. The electrochemical device according to claim 1, wherein Based on the mass of the first silicon-carbon composite material, the mass percentage of fluorine element is 0.05% to 2%.
9. The electrochemical device according to claim 1, wherein: The mass percentage of silicon in the first silicon-carbon particles is 38% to 50%, and the mass percentage of silicon in the second silicon-carbon particles is 42% to 60%.
10. The electrochemical device according to any one of claims 1 to 9, wherein: The compaction density of the negative electrode plate is 1.6 g / cm 3 Up to 1.8g / cm 3 .
11. The electrochemical device according to any one of claims 1 to 9, wherein: The electrolyte includes sulfolane, and based on the mass of the electrolyte, the mass percentage of sulfolane is 0.12% to 0.48%.
12. The electrochemical device according to any one of claims 1 to 9, wherein: The electrolyte includes fluoroethylene carbonate. Based on the mass of the electrolyte, the mass percentage of fluoroethylene carbonate is 8% to 20%, preferably 12.5% to 17.5%.
13. An electronic device comprising the electrochemical device according to any one of claims 1 to 12.